Interaction effects of night-time temperature and PM2.5 on preterm birth in Huai River Basin, China - Zhang, Huanhuan; Zhang, Xiaoan; Feng, Demin; Gao, Zhan; Gong, Yuting; Zhang, Junxi; Song, Shuaixing; Yu, Zengli; Huang, Cunrui (Environment international, 2023)
•Evidence of the effects of nighttime temperature extremes on PTB is scarce.•Third trimester nighttime heat and cold increased the risk of PTB and its subtypes.•We found synthetic effects of nighttime temperature extremes and PM2.5 on PTB. Nocturnal temperature is observed increasing with global warming. However, evidence on night-time non-optimal temperature on the risk of preterm birth (PTB) is limited, and the potential interactions with air pollution on PTB has not been well clarified. We therefore conducted a population-based retrospective cohort study to evaluate the effect of night-time temperature extremes on the risk of PTB and its interaction with air pollution. Records of 196,780 singleton births from 4 counties in Huai River Basin (2013–2018) were obtained. Gridded data on night-time temperature were collected from a high-quality Chinese Air Quality Reanalysis dataset. We used a multivariate logistic regression to evaluate the effects of night-time heat and cold exposure on the risk of PTB as well as its subtypes. Potential interactions between night-time temperature extremes and fine particulate matter < 2.5 µm (PM2.5) were examined using the relative excess risk due to interaction (RERI). We found that the risk of PTB was positively associated with third trimester night-time extremely heat and cold exposure, with adjusted OR of 1.898 (95 %CI: 1.655–2.177) and 2.044 (95 %CI: 1.786–2.339). Similar effects were observed for PTB subtypes, moderately PTB (mPTB) and very PTB (vPTB). Synergistic effects (RERI greater than 0) of each trimester night-time temperature extremes exposure and PM2.5 on PTB were observed. We identified consistent positive interactions between night-time temperature extremes and PM2.5 on mPTB. No significant interaction of night-time temperature extremes and PM2.5 on vPTB was found. In conclusion, this large retrospective cohort study found that third trimester night-time heat and cold exposure significantly increased the risk of PTB and its subtypes. There is a synergistic effect between night-time temperature extremes and high PM2.5 levels on PTB and mPTB. In the context of climate warming, our results add new evidence to the current understanding of night-time non-optimal temperature exposure on PTB.